Journalism and conflict in Indonesia from reporting violence to promoting peace - Sharp, Steve; T&F eBooks (Abingdon, Oxon : Routledge, 2013)
"This book examines, through the case study of Indonesia over recent decades, how the reporting of violence can drive the escalation of violence, and how journalists can alter their reporting practices in order to have the opposite effect and promote peace"--Supplied by publisher.
1. Introduction -- 2. Communication and culture -- 3. Media freedom and journalistic culture in post-New Order Indonesia -- 4. Violence, culture and national disintegration in Indonesia -- 5. Culture wars in Indonesia -- 6. Framing religious conflict -- 7. War and peace journalism.
Includes bibliographical references (p. [229]-252) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Journalism -- Social aspects -- Indonesia; Violence -- Press coverage -- Indonesia; Social conflict -- Press coverage -- Indonesia; Conflict management -- Press coverage -- Indonesia; Peace-building -- Press coverage -- Indonesia; Mass media and peace -- Indonesia; Electronic books